Therapeutic Hypothermia and Injection of MSCs Improve Heart Structure under Experimental Myocardial Infarction - Trofimova, Anna V.; Chizh, Nikolay A.; Belochkina, Irina V.; Volina, Viktoria V.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):166.